Coal In Appalachia : An Economic Analysis - Harvey, Curtis E. (Book collections on Project MUSE., 2015)
Coal, the nation's most abundant fossil fuel and the only one that is exported, represents one of our most valuable natural resources. This study undertakes a thorough review of the economics of the Appalachian coal industry. It establishes, first of all, the international framework within which the American and the Appalachian coal industry function. It next examines the underlying principles that govern the production of and the demand for coal. This demand is influenced not only by price but also by world politics, the economic well-being of dozens of countries, government regulation, and t.